Judaism, Liberalism, and Political Theology (Book collections on Project MUSE., 2014)
Judaism, Liberalism, and Political Theology provides the first broad encounter between modern Jewish thought and recent developments in political theology. In opposition to impetuous associations of Judaism and liberalism and charges that Judaism cannot engender a universal political order, the essays in this volume propose a new and richly detailed engagement between Judaism and the political. The vexed status of liberalism in Jewish thought and Judaism in political theology is interrogated with recourse to thinking from across the Continental tradition.